Respuesta :

7x= -42
X= -6

6y= -42
Y= -7
7x + 6y = -42
 For this case what you should do is see the intersections with each of the axes and then join the ordered pairs.
 We have then:
 For the x axis: 
 y = 0
 Substituting in the equation:
 7x + 6 (0) = - 42
 7x + 0 = -42
 x = -6
 For the y axis:
 x = 0
 Substituting in the equation:
 7 (0) + 6y = -42
 0 + 6y = -42
 y = -42 / 6
 y = -7
 We graph the ordered pairs:
 (x1, y1) = (- 6, 0)
 (x2, y2) = (0, -7)
 Answer:
 See attached graph.
Ver imagen carlosego